3409 The Power of Phenotypic Extremes in Detecting Novel Genetic Modifiers of Hemophilia. (27th March 2019) - Bentur, Ohad Shimshon; Coller, Barry S.
Abstract : OBJECTIVES/SPECIFIC AIMS: 1. To identify novel genetic modifiers that result in a mild bleeding phenotype in patients with FVIII <1%. 2. To examine the feasibility of a practice model that incorporates the principles and methods for both obtaining consent for NGS and returning individual research results from the sources described above. METHODS/STUDY POPULATION: 1. We plan a 3-step approach for identifying novel genetic modifiers of hemophilia: a. Obtain samples from individuals with an extremely mild bleeding phenotype: The study will be narrowed to patients with confirmed FVIII <1%, a null mutation in the gene for FVIII, and a mild bleeding phenotype according to a detailed bleeding history. b. Identify variants that modify phenotype: Whole exome sequencing will be performed, followed by a focused analysis of genes known or suspected to be involved in thrombosis and hemostasis and prediction of variant impact using algorithms that account for conservation and deleteriousness of all variants. c. Verify the impact of novel variants in independent samples: In silico (analyze genetic databases for suspected variants), in vivo (assess bleeding in animal models of hemophilia after introducing presumed modifier variants). 2. We will employ a model for obtaining informed consent and communicating individual genetic research results and results with potential clinical impact to research participants: a. The informed consent process will be performed after potential participants read a pamphlet entitled "Genetic Research at The Rockefeller University Hospital and Center for Clinical and Translational Science." The pamphlet includes 16 questions that the potential participants are urged to ask the investigator, including, "What will you look for in my genetic information?", "Will I receive results from this study?". Potential participants will also be informed of the meaning of clinically actionable variants, either pathogenic variants related to phenotype or secondary ("incidental") findings (i.e. variants unrelated to phenotype, the knowledge of which could lead to actions that may improve health). Participants who do not want to receive information about potentially actionable variants will be excluded from the study to avoid a situation where the investigator has clinically important information that cannot be shared with the participant. b. Genetic testing will be performed in a CLIA-certified lab to allow investigators to share the results with the study participants. c. Results will be reported to study participants according to a standard operating procedure (SOP) that classifies the report of variants according to the relation to phenotype and the pathogenic potential. d. Participant satisfaction with the informed consent process and the return of results will be assessed by a questionnaire for obtaining participants' perceptions of their research experience, based on a standard set of validated research participation experiences measures (Kost RG et al, J Clin Transl Sci. 2018;2:31). RESULTS/ANTICIPATED RESULTS: Samples from individuals with severe null mutation hemophilia and a mild bleeding phenotype will be enriched in genetic modifier variants. After completing participation, participants will express satisfaction with the informed consent process and the results of the return of genetic information. DISCUSSION/SIGNIFICANCE OF IMPACT: Genetic risk assessment to predict bleeding risk has the potential to provide hemophilia patients with tailored therapy, allowing for very early initiation of treatment (prophylactic thrice weekly IV administration of FVIII) in patients with a high bleeding risk and deferring this costly and burdensome treatment in patients who are expected to be mild bleeders. Genetic modifier variants of hemophilia may be found to predict thrombosis in non-hemophiliac patients and profoundly impact the treatment of venous thrombosis. A structured process for obtaining consent for NGS and return of genetic results to study participants can protect them from uncertain genetic information. Moreover, this process will prevent a situation in which investigators have knowledge about clinically actionable variants but they are not allowed to report them to the participants or do not have a process for doing so. Sharing individual research results and results with clinical significance with participants of studies that involve whole exome sequencing can promote transparency and engagement of participants throughout the research enterprise.